Heat transfer and mixing in flow through pinched pipe - Hasabnis, Nilesh S.; Totlani, Kartik A.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2015)
There is an increasing trend of using tubular reactors either with passive or active augmentation methods for process intensification. A new passive method with pinching of pipe' is proposed and investigated for its performance. In the present work, initially, flow in a pinched pipe was studied experimentally and the same was reproduced numerically. The computational model was then used to investigate influences of key geometrical parameters of pinched pipe configuration on pressure drop, heat transfer, and mixing. The simulated results obtained with the pinched pipe were compared with a straight pipe, and with a commonly-used passive augmentation method (twisted tape inserts). The pinched pipe configuration offers better performance and more flexibility in manipulating heat transfer and mixing in intensified devices.
Keywords: computational fluid dynamics (CFD); heat transfer; mixing; pinched pipe; pressure drop